Features and ways of improving the structure of competition law in Ukraine - Корчак, Н. М.; Головко, Ю. Ю. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
This work is devoted to the features of competition legislation in Ukraine, and also analizes some issuesof necessity of his improvement. An author pays attention to the necessity of determinationof priorities of defence of national commodity producers and national markets from the attempts of monopolization and discrimination of Ukraine at the international markets.